Fortune telling – palm print identification and analysis - Ng, Jing Jie. (2013)
Palm reading is one of the more popular and well known fortune telling techniques. It has always been in human nature to make services and goods more accessible and convenient for the customer/user. What better way to do that then to computerize the whole process and remove the human medium. With the whole palm reading process being converted into a user friendly program, anyone can get to enjoy the value this service can add to everyone’s life, be it in entertainment value or to aid in making decisions.